Harnessing the untapped potential of food education in schools: Nurturing the school subject Food and Health - Tormod Bjørkkjær; Päivi Palojoki; Cecilie Beinert (Wiley, 2024)
Abstract Essential life skills related to food and meals have a potential triple dividend for children and adolescents, that is, short‐term, medium‐term and possible generational effects with regard to public health, sustainability and well‐being of future citizens in local communities. While parents and childhood environments are a basis for learning about food and meals, systematic food education in the setting of primary and lower secondary schools may have a significant role that should be utilized more strongly, reaching and benefitting all pupils from a life course perspective. Through this article, we explore the current state of the art of the mandatory school subject Food and Health (FH) from the Nordic perspective. Our leading questions are: (1) What potential is currently utilized and which future potential does FH education have in primary and secondary schools in terms of food education for essential life skills and competencies, and (2) How can this untapped potential be better harnessed with a goal of facilitating better learning in FH? Drawing on data from Norway as a case study, supported by Swedish and Finnish data, we discuss the status, challenges and potential reformation of food education, focusing on FH. This includes perspectives on the prioritization of the FH subject and the organization of more systematic food education in schools, which might improve FH's status and significance. Combining theory-practice, creating room for discussion and focusing less on cooking‐related activities may better facilitate learning in FH. Without proper FH, food education might be nonsystematic, thereby generating unequal outcomes for children and adolescents.